Perbandingan Metode Fuzzy Tsukamoto dengan Fuzzy Mamdani Untuk Mendeteksi Tingkat Kecanduan Media Sosial Pada Remaja - Ariel Cahyono; Agung Triayudi; Rima Tamara Aldisa (Journal of Computer System and Informatics (JoSYC), 2023)
The level of social media use in Indonesia has increased every year. This is caused by several factors, one of which is the tendency to play social media so that you forget the time to do other activities such as studying. A system is needed that is able to detect whether someone is addicted to social media or not. The Tsukamoto fuzzy method is a method that can solve a problem by using a system on a computer in search of a truth and usually requires some expertise. While the fuzzy mamdani method has a function in finding a solution in solving the problem of social media addiction in today's youth. This comparison is done by the author to find the best answer from one of the methods used. This research was created in order to be able to detect the level of social media addiction in adolescents in the form of a web to inform adolescents to avoid the negative symptoms of social media addiction such as timelessness, lazy learning and being unable to stop oneself from controlling social media use. Then after testing with 25 adolescent data, the results obtained were 10 adolescents experiencing social media addiction problems and 15 adolescents not. It can be seen that the Tsukamoto method has a very addictive score of 0 to 20 for 10 teenagers and 15 teenagers with a non-addiction score of 80 to 100. Meanwhile, it is known that the Mamdani method has a very addictive score of 0 to 10 for 10 teenagers and 15 teenagers with a non-addicted score of 40 to 50.